USING PICTURES AS TEACHING MEDIA IN WRITING DESCRIPTIVE TEXT - Vanesa, Agis Putri; Setiawati, Pipih (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This research investigated “Using Picture as Teaching Media in Writing Descriptive Text”. It enhanced the ability to write descriptive in one of junior high school in Garut. The purpose of the research was to know the effect of using pictures on students’ writing ability in descriptive text. The research population was the eighth-grade students. The researcher used a written test to collect data. The research design was quantitative experimental. Data were collected through pre-test and post-test. The technique used in analyzing the data was t-test formula. It was used to determine whether there was a significance difference between the pre-test and post-test. The result of the test between pre-test and post-test, the mean of pre-test was 59.63 and the mean of post-test was 75.17 The obtained t- test was t observed = 12.51 and t critical = 2.0452. The result showed that t observed greater than t critical (12.51 > 2.0452). The t observed was in the area H0 rejected it means H0 was rejected so Ha was accepted. So, it can be concluded that using the pictures as teaching media is effective to develop students’ ability in writing descriptive text after being given the treatments. The result of the research was expected to consider teachers to practice the use pictures as teaching media in writing descriptive text. It would develop students’ writing skill easily.